Real-time assessment of eye movements during reading in individuals with central vision loss using eye-tracking technology: A pilot study - González Vides, Leonela Isarina (2025)
Purpose: To assess eye movements during reading in individuals with central vision loss using eye-tracking technology and an ad-hoc calibration method. Materials and methods: This pilot case control study included 17 participants (61.7 ± 8.8 years), 12 women and 5 men) and 17 controls, matched for age and sex. Two ad hoc computer-based tests were administered to analyze eye movements during a single-letter reading task and continuous reading task, measured using a 60 Hz eye-tracking device. Results: Individuals with central vision loss showed differences from the control group, with an increase in the number of fixations, saccadic movements, and regressions, whereas the amplitude and speed of saccades were lower. This resulted in longer reading times in the study group. Conclusion: The results revealed lower performance in eye movements skills during reading tasks in patients with central vision loss. Eye-tracking devices allow the objective binocular assessment of eye movements during reading tasks. Our ad-hoc calibration method ensured minimal data loss and high validity, enhancing the reliability of the assessments. This information can be used to develop optimal and personalized functional and visual rehabilitation programs.